Odpowiedź :
[tex]a)\\3x = 72 \ \ /:3\\\\x = 24\\\\\\b)\\\frac{3-x}{2} = \frac{1}{3} \ \ /\cdot6\\\\3(3-x) = 2\\\\9-3x = 2\\\\-3x = 2 - 9\\\\-3x = -7 \ \ /:(-3)\\\\x = \frac{7}{3} = 2\frac{1}{3}\\\\\\c)\\1-3x = \frac{1}{2}\\\\-3x = \frac{1}{2}-1\\\\-3x = -\frac{1}{2} \ \ /:(-3)\\\\x = \frac{1}{6}\\\\\\d)\\\frac{1}{2}x+1 = 4\\\\\frac{1}{2}x = 4-1\\\\\frac{1}{2}x = 3 \ \ /\cdot2\\\\x = 6[/tex]
a)
3x = 72
3x=72/:3
x=24
b)
3-x/2 = 1/3
-½x=⅓-3
-½x=-2 ⅔ I:(-½)
x=5⅓
c) 1 - 3x = 1/2
-3x=½-1
-3x=-½ /:(-3)
x=1/6
d) 1/2x + 1 = 4
½x=4-1
½x=3/:½
x=6